THE CULTURAL SIGNIFICANCE OF FISH IN INDIAN WRITING: A LITERATURE ATTEMPT OF UNDERSTANDING THE MATSYA INCARNATION (Journal of Pharmaceutical Negative Results, 2023)
Fish constitutes the most diverse and crucial part of the marine ecosystem. Not only it supports the economy and ecosystem but also has been a major influence in human culture and literature. Fishing is one of the most ancient professions and has been practiced for over 40000 years. Bay of Bengal is one such region which was initially at the heart of the fishing map but has been witnessing a gradual decline since the last century. Fishes have been a constant part of ritual and beliefs of worlds major culture and religions. Whether Hinduism, Buddhism, Christianity or Jewism, fishes have been a part of the practice and scared epics of these religions. The cultural impact of fishes is enormous and inseparable. Fish have been mentioned in the context of savior, beauty, illusion, and monsters. The folk tales, stories, cinemas, novels and astrology, astronomy and fantasies have been deeply influenced by these organisms. Matsya is Sanskrit name for fish and the earliest textual reference of Fish in human culture comes from Matsyaavatar in Hinduism. A complete purana known as Matsyapurana revolves around Lord Vishnu’s Matsyaavatar and preservation of the civilization during Pralaya or the great flood. The incarnation takes the form of half human and half fish (or a chimera), which is possibly the earliest reference to a Merman in any religious or non-religious text. In our study we have tried to understand the Matsyaavatar from the perspective of Fable genre of literature and its cultural influence on the society.